Hollow Mesoporous silica Nanoparticles Fabrication for anticancer Drug Delivery / Nguyen Thi Ngoc Tram, Nguyen Dai Hai - Nguyen, Thi Ngoc Tram
In this study, hollow mesoporous silaca nanoparticles were fabricated in order to increase the drug loading capacity of nanosilica materials